ANALYSIS OF STUDENT LEARNING OUTCOMES IN THE MINIMUM COMPETENCY ASSESSMENT AT SD INPRES 4 SAUSU - Ni Luh Tina Murniati; I Ketut Kertayasa; Ni Made Mega Hariani (STAH Dharma Sentana Sulawesi Tengah, 2023)
The purpose of this study was to determine student learning outcomes and the faktors that influence and the factors student learning outcomes in the Minimum Competency Assessment (AKM) in grade V SD Inpres 4 Sausu. Determination of informants by purposive sampling. The methods used were observation, interviews, test, and documentation. Based on the results of the numeracy type AKM test questions, student learning outcomes that are classified as low are 75%, classified as moderate are 25%, and classified as high are 0% where the dominant learning outcomes are classified as low categories. The faktors that influence student learning outcomes in the numeracy type AKM are internal faktors and external faktors. Internal factors that influence student learning outcomes in the numeracy type AKM are interests and talents. External factors that affect student learning outcomes in the numeracy type AKM are family faktors, school faktors, and community factors.